Starch rheological characterization and morphological evaluation of 20 varieties of Musaceae (Musa sp.), from Fedeplatano Germplasm Bank, Chinchiná - Caldas, Colombia - Juan Carlos Lucas Aguirre; Víctor Dumar Quintero Castaño (Acta Agronómica, 2016)
Twenty varieties of Musa the different genetic composition from Fedeplátano Germplasm Bank (AA, AAA, AAB, ABB, and AAAA AAAB) were characterized. Characterization includes physical properties such as weight, diameter, length, and dry matter percentage of fruit peel and functional properties of starches (pasting curves). The varieties Cachaco Pelipita, Fougamou, Kelong Mekintu and SH-3436-9 showed higher percentages of dry matter 35% indicating that these varieties would be of great importance for the sector fried and contain less water that the process be expedited increasing performance and decreasing absorption of oil. The varieties showed better behavior in relation to the properties of high viscosity, breakdown, ease of cooking and consistency were FHIA-23, Dwarf Banana, Banana Great Dwarf, Pompo Comino, indicating that these strains had great ability to withstand the retrogradation process and syneresis.